Analysis of Factors Influencing the Incidence of Stunting in Toddlers - Widyaningsih, Tri Sakti; Wulandari, Novita Kurnia; Kanita, Maria Wisnu (CV. Global Health Science Group, 2024)
Stunting is one of the problems that hinders human development globally. Currently, there are around 162 million children under the age of five experiencing stunting. If this continues, it is projected that in 2025 there will be 127 million children under the age of five who will experience stunting. The purpose of this study was to analyze the factors that influence the incidence of stunting in toddlers in the Banyuanyar Health Center Area. Research methodology: This study is an explanatory research study with a cross-sectional method approach. The sample of this study was approximately 56 toddlers at risk of stunting who were taken using a purposive technique by using the Slovin scale. Researchers took respondents based on inclusion and exclusion criteria during the implementation of the integrated health post, asked for respondents' approval, distributed research instruments and explained how to fill out the questionnaire. After obtaining the required data, researchers rechecked the questionnaire contents and then processed the data. The analysis used was the Chi Square test. Results of the study: Factors that influence the incidence of stunting in toddlers in the Banyuanyar Health Center Working Area, namely: History of LBW (p Value = 0.042), Provision of MP-ASI (p Value = 0.000), Mother's knowledge (p Value = 0.001), Parenting Patterns (p Value = 0.005). Factors that do not affect the incidence of stunting in toddlers in the Banyuanyar Health Center Work Area, namely: Exclusive Breastfeeding (p Value = 0.279), Immunization Status (p Value = 0.094), Socioeconomic (p value = 0.066). Conclusion: There are 4 factors that affect and 3 factors that do not affect the incidence of stunting in toddlers in the Banyuanyar Health Center Work Area, Surakarta City.